The Gold Living Life Resort: เดอะ โกลด์ ลิฟวิ่ง ไลฟ์ รีสอร์ท - Sangsuriya, Kritsada (Journal of Research Creative Architecture and Design, 2025)
Thung Song City, Chamai, Nakhon Si Thammarat Province is a “secondary city” where tourism is not yet widespread. It mainly serves as a stopover for travelers en route from Nakhon Si Thammarat. One of the key problems is that the design of hotels and resorts remains conventional, with rooms arranged in long, adjacent rows to meet legal requirements. The emphasis is often on maximizing the number of rooms, which compromises quality and makes the facilities less appealing to tourists. The project “The Gold Living Life Resort,” located in Thung Song city on an orange-zoned area of 2 rai and 1 ngan. The design is inspired by the concept of laminar airflow, which serves as the core idea for developing a new form of architectural design. By strategically spacing the buildings, green spaces are integrated into the layout, creating building gaps that allow natural wind flow to pass through the site efficiently. The project consists of 36 guest rooms, along with support areas and various building systems. The total building floor area is 1,187 square meters, while the landscaped area covers 2,689 square meters. Open space accounts for as much as 70% of the total site area. The design creates a cluster layout with a central courtyard. In addition to promoting effective natural ventilation, the building arrangement provides mutual shading, resulting in a cooler and more comfortable overall environment. The courtyard also functions as a seating area, enhancing the ambiance and supporting various activities. This has allowed the project to increase the value of its rooms beyond those of other accommodations in the area and attract tourist interest through its distinctive design and unique atmosphere.